The Existence of Legal Protection For Female Workers In The Informal Sector In Yogyakarta - Desmonda Amelinda, Ristia; Dyah Suprabowati, Gayatri (CV. Inara, 2025)
Informal sector female workers in Yogyakarta face various challenges in obtaining adequate legal protection. However, there are still various laws and regulations that provide protection for workers, but their implementation in the informal sector is still limited. The existence and continuity of informal sector activities in the economic system play a significant role in community development and national development. This study aims to identify various local government policies, as well as the implementation of relevant national regulations, such as “Law No. 13 of 2003 concerning Manpower”.The method used is normative juridical research, which is based on a statutory approach and a case approach. The results of the study indicate that although there have been efforts to provide legal protection through policies regulated by law, their implementation in the field is still limited, especially in terms of monitoring and awareness of female workers regarding their rights.